Light-emitting device, preparation method thereof and display device

The electron transport layer was prepared by the sol-gel method and the low-temperature alcohol phase method, which solved the problems of uneven interface of the nano zinc oxide layer and poor electron injection properties, and improved the luminescence efficiency and life of the light emitting device.

CN119317339APending Publication Date: 2025-01-14TCL TECHNOLOGY GROUP CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310848986.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In existing light-emitting devices, the nano zinc oxide layer has uneven interfaces and poor electron injection properties, which affects the performance of the light-emitting device.

Method used

The first electron transport layer is formed by the sol-gel method, and the second electron transport layer is prepared by the low-temperature alcohol phase method. The second electron transport layer is arranged near the light emitting layer to improve the mobility and interface contact of the electronic functional layer and reduce the Exciton dissociation.

Benefits of technology

It improves the luminous efficiency and life of the light emitting device, enhances the mobility of the electronic functional layer and the interface contact flatness, and improves the overall performance of the light emitting device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119317339A_ABST
    Figure CN119317339A_ABST
Patent Text Reader

Abstract

The invention discloses a light-emitting device, a preparation method thereof and a display device. According to the light-emitting device, the first electron transport layer is formed through the sol-gel method, and the electronic functional layer comprising the first electron transport layer and the second electron transport layer is formed, so that the electron mobility of the electronic functional layer can be improved, and the interface contact performance can be improved; therefore, the composite efficiency and luminous efficiency of the light-emitting device are improved, and the service life of the light-emitting device is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of optoelectronic technology, and in particular to a light-emitting device and a method for preparing the same, and a display device. Background Art

[0002] The light-emitting devices widely used at present are organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs). The traditional OLED and QLED device structures mainly include cathodes, anodes, hole functional layers, light-emitting layers, and electron functional layers. Under the action of the electric field, the holes generated by the anode of the light-emitting device and the electrons generated by the cathode move and are injected into the hole transport layer and the electron transport layer respectively, and finally migrate to the light-emitting layer. When the two meet in the light-emitting layer, energy excitons are generated, and finally visible light is generated.

[0003] In current light-emitting devices, nano zinc oxide (ZnO) is widely used as an electron transport material because its conduction band energy level is conducive to the injection of electrons from the cathode to the quantum dots, and its deeper valence band energy level can effectively block holes. However, the zinc oxide layer as an electron transport layer also has potential disadvantages such as uneven interface and poor electron injection, which affect the performance of light-emitting devices. Summary of the invention

[0004] In view of this, the present application provides a light-emitting device and a method for preparing the same, and a display device, aiming to improve the performance of the light-emitting device.

[0005] The embodiment of the present application is implemented as follows: a method for preparing a light-emitting device is provided, the method comprising: providing a preset device, the preset device comprising a second electrode; arranging an electronic functional layer on the preset device; arranging a light-emitting layer and a first electrode in sequence on the side of the electronic functional layer away from the second electrode; or, the method comprising: providing a preset device, the preset device comprising a first electrode and a light-emitting layer; arranging an electronic functional layer on the preset device; arranging the second electrode on the side of the electronic functional layer away from the light-emitting layer; wherein the electronic functional layer comprises a first electron transport layer and a second electron transport layer; arranging the electronic functional layer on the preset device comprises: forming the first electron transport layer by a sol-gel method, and forming the second electron transport layer, wherein the second electron transport layer is arranged close to the side of the light-emitting layer, and the first electron transport layer is arranged away from the side of the light-emitting layer.

[0006] Optionally, in some embodiments of the present application, the formation of the first electron transport layer by a sol-gel method includes: providing a first solution, the first solution including a first metal source, an organic amine and a first solvent; refluxing the first solution to obtain a first sol; setting the first sol on the second electrode or the second electron transport layer to form a wet film, and annealing to obtain the first electron transport layer.

[0007] Optionally, in some embodiments of the present application, the first metal source includes a first zinc source and a first doping metal source; further, the first zinc source includes one or more of diethyl zinc, zinc oleate, zinc stearate, zinc acetate, zinc laurate and zinc oxide; and / or, the first doping metal source includes one or more of Li source, Be source, Mg source, Al source, K source, Ca source; and / or, the molar ratio of the zinc element in the first zinc source to the first doping metal element in the first doping metal source is (3 to 100): 1; and / or, in the first solution, the total molar concentration of the zinc element in the first zinc source and the first doping metal element in the first doping metal source is 0.1 to 1 mmol / mL; and / or, the organic amine includes one or more of ethanolamine, diethanolamine, 3-aminopropanol; and / or, the molar ratio of the organic amine to the first metal source is 1:1.3 to 1.3:1; and / or, the first solvent is selected from alcohol solvents.

[0008] Optionally, in some embodiments of the present application, the temperature of the reflux reaction is 50-80°C; and / or, the time of the reflux reaction is 3-12h; and / or, the temperature of the annealing treatment is 150-500°C; and / or, the time of the annealing treatment is 5-120min.

[0009] Optionally, in some embodiments of the present application, the forming of the second electron transport layer includes: providing a second solution, wherein the second solution includes zinc oxide nanomaterial and a second solvent; and disposing the second solution on the light-emitting layer or the first electron transport layer to obtain the second electron transport layer.

[0010] Optionally, in some embodiments of the present application, the zinc oxide nanomaterial is selected from zinc oxide or doped zinc oxide, wherein the doped zinc oxide includes zinc oxide and a second doping element, and the second doping element is selected from one or more of Mg, Ga, Al, Mn, and In; and / or, the second solvent is selected from an alcohol solvent; and / or, in the second solution, the concentration of the zinc oxide nanomaterial is 10 to 50 mg / mL; and / or, the zinc oxide nanomaterial is prepared by a low-temperature alcohol phase method.

[0011] Correspondingly, an embodiment of the present application further provides a light-emitting device, which is manufactured by the above-mentioned method for manufacturing a light-emitting device.

[0012] Optionally, in some embodiments of the present application, the thickness of the first electron transport layer is 5 to 40 nm; and / or the thickness of the second electron transport layer is 5 to 40 nm.

[0013] Optionally, in some embodiments of the present application, the material of the light-emitting layer is selected from one or more of organic light-emitting materials or quantum dot light-emitting materials; the organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light and DBP fluorescent materials emitting red light; the quantum dot light-emitting material is selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, and the single-structure quantum dots are selected from II-VI compounds, IV-VI compounds, III-V compounds and I-III- At least one of the Group VI compounds, the Group II-VI compound being selected from the group consisting of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, At least one of HgZnSeS, HgZnSeTe and HgZnSTe, the IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, at least one of GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the Group I-III-VI compound is at least one of CuInS, CuInSe and AgInS;The core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2 + , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; and / or,

[0014] The first electrode and the second electrode are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, ITZO, ICO, At least one of AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS; and / or,

[0015] The light-emitting device further comprises a hole functional layer, which is arranged between the first electrode and the light-emitting layer. The hole functional layer comprises at least one layer of a hole injection layer and a hole transport layer. The material of the hole transport layer is selected from arylamine, polyaniline, polypyrrole, poly(p-phenylene vinylene) and its derivatives, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinyl carbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octyl)-1,1'-biphenyl compound, poly(p-carbazolyl ... Fluorene) and its derivatives, poly (spirofluorene) and its derivatives, doped or undoped NiO, MoO3, WO3, V2O5, CrO3, CuO, MoS2, MoSe2, WS3, WSe3, CuS, CuSCN one or more; wherein the aromatic amine is selected from 4,4'-bis (9-carbazole) biphenyl, poly (9,9-dioctylfluorene-CO-N- (4-butylphenyl) diphenylamine), poly (N,N'-bis (4-butylphenyl) -N,N'-bis (phenyl) benzidine), N,N'-bis (4- (N,N'-diphenyl-amino) phenyl )-N,N'-diphenylbenzidine, poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine), 4,4',4"-tri(carbazol-9-yl)triphenylamine, 4,4',4"-tri(N-carbazolyl)-triphenylamine, 4,4',4"-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'- One or more of diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, Spiro-NPB, Spiro-TPD, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, Spiro-NPB; the poly(p-)phenylene vinylene and its derivatives are selected from one or more of poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene];The material of the hole injection layer is selected from poly(ethylenedioxythiophene): polystyrene sulfonate, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, copper phthalocyanine, poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl, 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine, 4,4' ,4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with F4-TCNQ, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, transition metal oxides, transition metal sulfur compounds; wherein the transition metal oxides include one or more of NiO, MoO2, WO3, and CuO; the metal sulfur compounds include one or more of MoS2, MoSe2, WS3, WSe3, and CuS.;

[0016] Correspondingly, an embodiment of the present application further provides a display device, comprising the above-mentioned light-emitting device.

[0017] The light-emitting device of the present application forms the first electron transport layer by a sol-gel method, and forms an electronic functional layer including the first electron transport layer and the second electron transport layer, which can improve the mobility of the electronic functional layer and improve the interface contact, thereby improving the luminous efficiency of the light-emitting device and increasing the life of the light-emitting device. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 A schematic diagram of a process of an embodiment of a method for preparing a light-emitting device provided in the present application;

[0020] Figure 2 A schematic diagram of another embodiment of a method for preparing a light-emitting device provided in the present application;

[0021] Figure 3A structural schematic diagram of an embodiment of a light emitting device is provided for the present application.

[0022] Reference numerals: 100 - light-emitting device; 10 - first electrode; 20 - second electrode; 30 - light-emitting layer; 40 - electron functional layer; 41 - first electron transport layer; 42 - second electron transport layer; 50 - hole functional layer. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application. In the present application, unless otherwise specified, the directional words such as "upper" and "lower" used are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may exist in the form of a range; it should be understood that the description in the form of a range is only for convenience and simplicity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single values ​​within the range. For example, description of a range from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the stated range, such as 1, 2, 3, 4, 5, and 6, regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited numeral (fractional or integral) within the stated range.

[0024] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0025] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0026] The present application provides a method for preparing a light emitting device. Figure 1 , Figure 1 The present invention provides a flow chart of a method for preparing a light-emitting device according to an embodiment of the present invention, which specifically includes the following steps:

[0027] Step S11: providing a preset device, wherein the preset device includes a second electrode;

[0028] Step S12: providing an electronic functional layer on the preset device;

[0029] Step S13: sequentially disposing a light-emitting layer and a first electrode on a side of the electronic functional layer away from the second electrode.

[0030] The light-emitting device prepared in this embodiment is an inverted device.

[0031] See also Figure 2 , Figure 2 A schematic flow chart of another embodiment of a method for preparing a light-emitting device provided in the present application specifically includes the following steps:

[0032] Step S21: providing a preset device, wherein the preset device includes a stacked first electrode and a light-emitting layer;

[0033] Step S22: providing an electronic functional layer on the preset device;

[0034] Step S23: forming a second electrode on a side of the electronic functional layer away from the light-emitting layer.

[0035] The light-emitting device prepared in this embodiment is an upright device.

[0036] In step S12 and step S22, forming an electronic functional layer on the preset device includes:

[0037] A first electron transport layer is formed, and a second electron transport layer is formed, wherein the second electron transport layer is formed on a side close to the light-emitting layer, and the first electron transport layer is formed on a side away from the light-emitting layer.

[0038] The forming of the first electron transport layer is prepared by a sol-gel method, which specifically includes:

[0039] Step S31: providing a first solution, wherein the first solution comprises a first metal source, an organic amine and a first solvent; wherein the first metal source comprises a first zinc source and a first doping metal source;

[0040] Step S32: subjecting the first solution to a reflux reaction to obtain a first sol;

[0041] Step S33: preparing the first sol and performing annealing treatment to obtain the first electron transport layer.

[0042] In one embodiment, the second electron transport layer is formed by a solution process, comprising:

[0043] Step S41: providing a second solution, wherein the second solution includes zinc oxide nanomaterial and a second solvent;

[0044] Step S42: preparing the second solution to obtain the second electron transport layer.

[0045] In this embodiment, the first electron transport layer is prepared by a sol-gel method, specifically: the first solution in which each material is evenly mixed is subjected to a reflux reaction, and after chemical reactions such as hydrolysis and condensation, the first solution forms a stable transparent sol system, that is, the first sol is obtained, and after the first sol is set to form a liquid film layer, the first sol will gradually form a gel, and after the annealing treatment, it will solidify to form a dry nanomaterial film layer, thereby obtaining the first electron transport layer. On the one hand, the sol-gel method can significantly improve the crystallinity of the first electron transport layer, thereby improving the electron mobility of the first electron transport layer; on the other hand, the sol-gel method can achieve effective doping of the first doped metal element in the first electron transport layer, thereby improving the electron mobility. The second electron transport layer is provided by a conventional solution method, and has good flatness and film-forming properties, thereby improving the interface contact between the second electron transport layer and the light-emitting layer and between the second electron transport layer and the first electron transport layer, avoiding the influence of the unevenness of the contact interface on the transmission and injection of electrons, and reducing the dissociation of excitons at the quantum dot / zinc oxide interface, thereby improving the recombination efficiency and luminescence efficiency of the light-emitting device, and also improving the life of the light-emitting device.

[0046] In step S31:

[0047] The first zinc source may include one or more of diethyl zinc, zinc oleate, zinc stearate, zinc acetate, zinc laurate, zinc oxide, and the like.

[0048] The first doping metal source includes one or more of a Li source, a Be source, a Mg source, an Al source, a K source, and a Ca source.

[0049] It can be understood that the radius of the first doping metal element corresponding to the first doping metal source is small, and the interstitial zinc defects can be eliminated by interstitial doping. The first electron transport layer is arranged in contact with the second electrode, which can improve the conductivity and electron mobility without changing the work function and valence band edge.

[0050] Specifically, the Li (lithium) source includes one or more of lithium acetate and its hydrate, lithium nitrate and its hydrate, lithium sulfate and its hydrate, lithium chloride and its hydrate, and the like.

[0051] The Be (beryllium) source includes one or more of beryllium acetate and its hydrate, beryllium nitrate and its hydrate, beryllium sulfate and its hydrate, beryllium chloride and its hydrate, and the like.

[0052] The Mg source includes one or more of magnesium acetate and its hydrate, magnesium nitrate and its hydrate, magnesium sulfate and its hydrate, magnesium chloride and its hydrate, and the like.

[0053] The Al source includes one or more of aluminum acetate and its hydrate, aluminum nitrate and its hydrate, aluminum sulfate and its hydrate, aluminum chloride and its hydrate, and the like.

[0054] The K source includes one or more of potassium acetate and its hydrate, potassium nitrate and its hydrate, potassium sulfate and its hydrate, potassium chloride and its hydrate, and the like.

[0055] The Ca source includes one or more of calcium acetate and its hydrate, calcium nitrate and its hydrate, calcium sulfate and its hydrate, calcium chloride and its hydrate, and the like.

[0056] The molar ratio of the zinc element in the first zinc source to the first doping metal element in the first doping metal source is (3-100):1, and can be specifically (3-80):1, (10-80):1, (10-60):1, (30-60):1, (30-50):1, (40-50):1, etc.

[0057] In one embodiment, in the first solution, the molar concentration of the total metal elements contained in the first metal source is 0.1-1 mmol / mL, specifically 0.1-0.85 mmol / mL, 0.25-0.85 mmol / mL, 0.25-0.5 mmol / mL, etc. The total metal elements include the zinc element in the first zinc source and the first doping metal element in the first doping metal source. The concentration is conducive to the formation of a sol, has good dispersibility in the process of forming the first electron transport layer, and improves the film-forming property of the first electron transport layer.

[0058] The organic amine may include one or more of ethanolamine, diethanolamine, 3-aminopropanol, etc. The organic amine may be used as a stabilizer when the first solution is subjected to a reflux reaction, and the stabilizer may complex with the precursor to improve the dispersion and stability of the precursor and prevent agglomeration during the system reflux.

[0059] In one embodiment, the molar ratio of the organic amine to the first metal source is 1:1.3 to 1.3:1, specifically 1:1.3 to 1.2:1, 1:1.2 to 1.2:1, 1:1.2 to 1.1:1, 1:1.1 to 1.1:1, 1:1.1 to 1.1, etc.

[0060] The first solvent may be selected from alcohol solvents, and specifically may include one or more of ethanol, isopropanol, n-butanol, 2-methoxyethanol, etc. In a specific embodiment, the first solvent is 2-methoxyethanol.

[0061] In step S32:

[0062] In one embodiment, the reflux reaction temperature may be 50-80° C., specifically 50-75° C., 55-75° C., 55-70° C., 60-70° C., 60-65° C., etc. The first solution undergoes a reflux reaction within the above temperature range to gradually form a clear first sol.

[0063] In one embodiment, the reflux reaction time may be 3 to 12 hours, specifically 3 to 10 hours, 5 to 10 hours, 5 to 8 hours, etc.

[0064] In one embodiment, the reflux reaction is performed under an inert gas atmosphere. Specifically, the inert gas atmosphere is an atmosphere in which an inert gas is used as a protective gas, such as nitrogen, argon, etc.

[0065] In step S33:

[0066] The annealing treatment temperature is 150-500° C., specifically 150-200° C., 200-300° C., 300-400° C., 400-500° C., etc. The annealing treatment at the above high temperature can significantly improve the crystallinity of the first electron transport layer, thereby improving the electron mobility of the first electron transport layer.

[0067] Furthermore, the annealing treatment time may be 5 to 120 minutes, specifically 5 to 30 minutes, 30 to 60 minutes, 60 to 90 minutes, 90 to 120 minutes, etc.

[0068] In one embodiment, the annealing process may be performed in a dry atmosphere, wherein the dry atmosphere contains oxygen, so as to form the zinc oxide nanomaterial including the first doped metal. Specifically, the dry atmosphere may be a dry air atmosphere.

[0069] In one embodiment, the thickness of the formed first electron transport layer is 5-40 nm, specifically 5-35 nm, 10-35 nm, 10-30 nm, 15-30 nm, 15-25 nm, 20-25 nm, etc.

[0070] In the step S41:

[0071] The zinc oxide nanomaterial can be selected from zinc oxide or doped zinc oxide. The doped zinc oxide includes zinc oxide and a second doping element, and the second doping element can be selected from one or more of Mg, Ga, Al, Mn, and In. The doping of the second doping element can improve the conduction band energy level of the zinc oxide material, thereby inhibiting the dissociation of excitons at the interface layer between the light-emitting layer and the electronic functional layer, thereby improving the recombination efficiency and luminous efficiency of the light-emitting device, and also improving the life of the light-emitting device.

[0072] The second solvent is selected from alcohol solvents, and specifically may include one or more of ethanol, isopropanol, n-butanol, 2-methoxyethanol, and the like.

[0073] In the second solution, the concentration of the zinc oxide nanomaterial is 10-50 mg / mL, specifically 10-45 mg / mL, 15-45 mg / mL, 15-40 mg / mL, 20-40 mg / mL, 20-35 mg / mL, 25-35 mg / mL, etc.

[0074] In one embodiment, the zinc oxide or doped zinc oxide is prepared by a low temperature alcohol phase method. Specifically, the preparation of zinc oxide or doped zinc oxide specifically includes the following steps:

[0075] Step S411: providing a third solution, wherein the third solution includes a second metal source and a third solvent, wherein the second metal source includes a second zinc source or the second metal source includes a second zinc source and a second doping metal source;

[0076] Step S412: adding alkali to the third solution, mixing and reacting at room temperature to obtain zinc oxide or doped zinc oxide.

[0077] In step S411:

[0078] The second zinc source includes one or more of diethyl zinc, zinc oleate, zinc stearate, zinc acetate, zinc laurate and the like.

[0079] The molar ratio of the zinc element in the second zinc source to the doping metal element in the second doping metal source is (3-100):1, and can be specifically (3-80):1, (10-80):1, (10-60):1, (30-60):1, (30-50):1, (40-50):1, etc.

[0080] It can be understood that the second doping metal source selects a corresponding metal salt according to the type of the doping metal, which is not limited here.

[0081] In one embodiment, the second doping metal source includes one or more of a Mg source, a Ga source, an Al source, a Mn source, an In source, and the like.

[0082] Specifically, each of the second doping metal sources can be selected from corresponding metal salts and their hydrates. In a specific embodiment, the doping metal source is a magnesium (Mg) source, and the magnesium source includes one or more of magnesium acetate and its hydrate, magnesium nitrate and its hydrate, magnesium sulfate and its hydrate, and magnesium chloride and its hydrate.

[0083] The third solvent may include one or more of dimethyl sulfoxide, NN-dimethylformamide, tetrahydrofuran, and alcohol solvents, wherein the alcohol solvent includes one or more of methanol, ethanol, isopropanol, and the like.

[0084] It is understandable that the third solvent may also include a ligand solvent, and the type of the ligand solvent may be set accordingly according to the ligand requirements of the zinc oxide or doped zinc oxide, and is not limited here. For example, a ligand solvent that improves solubility or reduces surface defects of the zinc oxide or doped zinc oxide may be included.

[0085] In one embodiment, providing the third solution specifically includes: mixing the second metal source and the third solvent, and stirring at room temperature for 1 to 8 hours to obtain the third solution.

[0086] In step S412:

[0087] The base may include one or more of lithium hydroxide, sodium hydroxide, triethylamine, ammonia water, tetramethylammonium hydroxide and hydrates thereof.

[0088] It will be appreciated that the base may be added in the form of a base solution.

[0089] In one embodiment, adding a base to the third solution comprises: adding the base to a fourth solvent, stirring at room temperature for 1 to 8 hours to obtain a base solution, and then adding the base solution. The base solution may also be referred to as an oxygen precursor.

[0090] Further, the fourth solvent may be selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide, tetrahydrofuran, alcohol solvents, etc., wherein the alcohol solvent includes one or more of methanol, ethanol, isopropanol, etc. Specifically, the solvent contained in the alkaline solution may also be of the same type as the third solvent.

[0091] In one embodiment, the mixing reaction time may be 1 to 48 hours, specifically 1 to 10 hours, 10 to 20 hours, 20 to 30 hours, 30 to 40 hours, 40 to 48 hours, etc.

[0092] In one embodiment, after the mixing reaction, the method further comprises: using a cleaning solvent for cleaning and purification to obtain the zinc oxide or doped zinc oxide. The cleaning solvent may include a mixture of one or more alcohol solvents and alkane solvents, such as one or more of ethanol, isopropanol, n-hexane and n-heptane.

[0093] In step S42:

[0094] After the second solution is set, drying is further performed to remove the solvent to obtain the second electron transport layer. The drying can be heating drying, the heating drying temperature is 60 to 150° C., and the time is 1 min to 30 min. The drying can be vacuum drying, and the vacuum drying pressure is 10 -1 ~10 -2 Pa, the temperature is 0-30°C, for example, it can be at room temperature of about 25°C.

[0095] In one embodiment, the thickness of the formed second electron transport layer is 5-40 nm, specifically 5-35 nm, 10-35 nm, 10-30 nm, 15-30 nm, 15-25 nm, 20-25 nm, etc.

[0096] In one embodiment, the method for preparing the light-emitting device further includes: forming a hole functional layer between the light-emitting layer and the first electrode.

[0097] The hole functional layer may include a hole injection layer and / or a hole transport layer. When the hole functional layer includes a hole injection layer and a hole transport layer, the hole injection layer is disposed close to the first electrode, and the hole transport layer is disposed close to the light emitting layer.

[0098] In one embodiment, the thickness of the hole injection layer may be 20-200 nm, specifically 20-150 nm, 80-150 nm, 80-120 nm, etc. The thickness of the hole transport layer may be 30-180 nm, specifically 30-150 nm, 50-150 nm, 50-120 nm, 80-120 nm, 80-100 nm, etc.

[0099] The material of the hole transport layer is selected from arylamine, polyaniline, polypyrrole, poly(p-)phenylene vinylene and its derivatives, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinylcarbazole) (PVK) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped or undoped NiO, MoO3, WO3, V2O5, CrO3, CuO, MoS2, MoSe2, WS3, WSe 3. One or more of CuS and CuSCN; wherein the aromatic amine is selected from 4,4'-bis(9-carbazole)biphenyl (CBP), poly(9,9-dioctylfluorene-co-N-(4-butylphenyl)diphenylamine) (TFB), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (poly-TPD), N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine (DNTPD), poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine) (PFB), 4,4', 4"-Tris(carbazol-9-yl)triphenylamine (TCATA), 4,4',4"-tris(N-carbazol-9-yl)triphenylamine (TCTA), 4,4',4"-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine (TPD), N,N'-diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine (TPD), One or more of 4'-diamine (NPB), Spiro-NPB, Spiro-TPD, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), and spiro-NPB; the poly(p-)phenylene vinylene and its derivatives are selected from one or more of poly(phenylene vinylene) (PPV), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEH-PPV) and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene] (MOMO-PPV).

[0100] The material of the hole injection layer is a material with hole injection ability, selected from poly(ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane (F4-TCNQ), 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HATCN), copper phthalocyanine (CuPc), Poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine ( m-MTDATA), 4,4',4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane (TAPC), 4,4',4"-tri(diphenylamino)triphenylamine (TDATA) doped with F4-TCNQ, p-doped phthalocyanine (e.g., F4-TCNQ-doped zinc phthalocyanine (ZnPc)), F4-TCNQ-doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), transition metal oxides, transition metal sulfur compounds; wherein the transition metal oxides include one or more of NiO, MoO2, WO3, CuO; the metal sulfur compounds include one or more of MoS2, MoSe2, WS3, WSe3, CuS.

[0101] In one embodiment, the material of the light-emitting layer is selected from one or more of organic light-emitting materials or quantum dot materials.

[0102] The organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distyrene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light, and DBP fluorescent materials emitting red light.

[0103] The quantum dot material can be selected from at least one of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The single structure quantum dot is selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound. The II-VI group compound is selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, Cd At least one of ZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound is selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnP bTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V compound is selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, At least one of GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound is selected from at least one of CuInS, CuInSe and AgInS; the core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS;

[0104] The perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - When n=2, the inorganic metal halide octahedron MX6 4- The metal cation M is located at the center of the halogen octahedron, and the organic amine cation B fills the gap between the octahedrons to form an infinitely extended three-dimensional structure. When n>2, the inorganic metal halide octahedron MX6 connected by the top-sharing method 4- It extends in two dimensions to form a layered structure, with an organic amine cation bilayer (protonated monoamine) or an organic amine cation monolayer (protonated diamine) inserted between the layers, and the organic layer and the inorganic layer overlap to form a stable two-dimensional layered structure.

[0105] In a specific embodiment, the material of the light-emitting layer is selected from the quantum dot material.

[0106] In one embodiment, the thickness of the light-emitting layer may be 15 to 40 nm, specifically 15 to 35 nm, 25 to 35 nm, 25 to 30 nm, etc.

[0107] In one embodiment, the first electrode and the second electrode are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, ITZ O, ICO, AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, Ga:SnO2; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS and ZnS / Al / ZnS. Wherein, " / " represents a stacked structure, for example, the composite electrode AZO / Ag / AZO represents an electrode of a composite structure of three stacked layers consisting of an AZO layer, an Ag layer and an AZO layer.

[0108] In one embodiment, the first electrode is composed of a conductive material having a relatively high work function, and may be composed of a doped or undoped metal oxide, such as ITO, IZO, ITZO, ICO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, Ga:SnO2 or AZO, etc.; or in addition to the above-mentioned metal oxides, it may be composed of a metal material including nickel (Ni), platinum (Pt), gold (Au), silver (Ag), iridium (Ir) or CNT.

[0109] In one embodiment, the second electrode is composed of a conductive material with a relatively low work function, which may be one or more of Ca, Ba, Ca / Al, LiF / Ca, LiF / Al, BaF2 / Al, CsF / Al, CaCO3 / Al, BaF2 / Ca / Al, Al, Mg, Au:Mg or Ag:Mg.

[0110] The light emitting device further comprises a substrate (not shown), which may also be referred to as a substrate. The substrate may be a rigid substrate or a flexible substrate. The rigid substrate may be a ceramic material or various glass materials. The flexible substrate may be a substrate formed of materials such as polyimide film (PI) and its derivatives, polyethylene naphthalate (PEN), phosphoenolpyruvic acid (PEP) or diphenylene ether resin. In one embodiment, the material of the substrate comprises glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide, polyether sulfone, or a combination thereof.

[0111] It can be understood that when the first electrode or the second electrode is connected to the substrate, it can be called a bottom electrode, and the one away from the substrate is a top electrode, wherein the thickness of the bottom electrode can be 20 to 200 nm, and the thickness of the top electrode can be 40 to 190 nm.

[0112] It can be understood that the light emitting device can be an upright light emitting device or an inverted light emitting device. When the light emitting device is an upright light emitting device, the substrate is combined with a side of the first electrode away from the light emitting layer. When the light emitting device is an inverted light emitting device, the substrate is combined with a side of the second electrode away from the light emitting layer.

[0113] It is understood that, in addition to the above-mentioned functional layers, the light-emitting device may also be provided with some functional layers conventionally used in light-emitting devices that help improve the performance of the light-emitting device, such as an electron blocking layer, an electron injection layer, a hole blocking layer and / or an interface modification layer, etc. Correspondingly, the method for preparing the light-emitting device also includes the preparation of the corresponding functional layers.

[0114] It can be understood that the material and thickness of each layer of the light-emitting device can be set and adjusted accordingly according to the light-emitting requirements of the light-emitting device.

[0115] In the light-emitting device provided in the present application, the preparation of the first electrode, the second electrode, the light-emitting layer, the hole functional layer and other film layers can be achieved by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction method, first electrode oxidation method, electrolytic deposition method, and coprecipitation method. The physical method includes physical plating method and solution method, among which the physical plating method includes: thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion plating method, physical vapor deposition method, atomic layer deposition method, pulsed laser deposition method, etc.; the solution method can be spin coating, printing method, inkjet printing method, scraping method, printing method, dip pulling method, immersion method, spraying method, roll coating method, casting method, slit coating method and strip coating method, etc.

[0116] It is understandable that the method for preparing the light-emitting device may further include a packaging step, and the packaging step may refer to packaging methods known in the art. For example, the packaging material used for packaging may be selected from at least one of UV glue, metal film, and glass glue. In a specific embodiment, the packaging material may be acrylic resin or epoxy resin. The packaging may be machine packaging or manual packaging, and may be sealed with ultraviolet curing glue. The concentration of oxygen and water in the environment of the packaging step is less than 0.1ppm to ensure the stability of the light-emitting device.

[0117] The present application also provides a light-emitting device, which is prepared by the method for preparing a light-emitting device provided by the present application. Figure 3 , Figure 3 The present application provides a structural schematic diagram of an embodiment of a light-emitting device, wherein the light-emitting device 100 includes a first electrode 10 and a second electrode 20 that are relatively arranged, and a light-emitting layer 30 that is arranged between the first electrode 10 and the second electrode 20, and an electronic functional layer 40 that is arranged between the second electrode 20 and the light-emitting layer 30.

[0118] The electronic functional layer 40 includes a first electron transport layer 41 and a second electron transport layer 42 . The first electron transport layer 41 is disposed close to the second electrode 20 , and the second electron transport layer 42 is disposed close to the light emitting layer 30 .

[0119] In this embodiment, the first electron transport layer 41 is prepared by a sol-gel method, which can make the first electron transport layer 41 have good crystallinity and thus good electron mobility; on the other hand, it can achieve effective doping of the first doping element in the first electron transport layer 41, and the first electron transport layer 41 is arranged in contact with the second electrode 20, which can improve the conductivity without changing the work function and the valence band edge, thereby also improving the electron mobility. The second electron transport layer 42 is arranged by a conventional solution method, has good flatness and film forming properties, improves the interface contact between the second electron transport layer 42 and the light-emitting layer 30 and between the second electron transport layer 42 and the first electron transport layer 41, avoids the unevenness of the contact interface affecting the transmission and injection of electrons, reduces the dissociation of excitons at the quantum dot / zinc oxide interface, thereby improving the recombination efficiency and luminescence efficiency of the light-emitting device 100, and also improves the life of the light-emitting device 100.

[0120] Furthermore, the light-emitting device further includes a hole functional layer 50 , and the hole functional layer 50 is disposed between the first electrode 10 and the light-emitting layer 30 .

[0121] Specifically, the light-emitting device 100, the first electrode 10, the second electrode 20, the light-emitting layer 30, the electron functional layer 40, the hole functional layer 50, etc. can all refer to the relevant description in the above-mentioned method for preparing the light-emitting device, and will not be repeated here.

[0122] The present application also relates to a display device, which includes the light-emitting device provided in the present application. The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptop computers, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, wherein the smart wearable device can be, for example, a smart bracelet, a smart watch, a virtual reality (VR) helmet, etc.

[0123] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0124] Device Example 1

[0125] The device embodiment provides a quantum dot light emitting diode and a method for preparing the same, which specifically includes the following steps.

[0126] Step 1: Add 0.5mmol zinc acetate dihydrate and 0.05mmol lithium acetate to 30mL 2-methoxyethanol, then add 0.5mmol ethanolamine as a stabilizer, reflux at 50°C for 8 hours under an inert gas atmosphere, cool the solution after clarification to obtain a sol. Provide a substrate with a bottom electrode (second electrode), deposit the above sol on the bottom electrode to form a film, heat at 300°C in dry air for 10mins and then anneal to obtain a first electron transport layer with a thickness of 15nm.

[0127] Step 2: Add 10mmol zinc acetate dihydrate and 1mmol magnesium acetate tetrahydrate to 30ml dimethyl sulfoxide, stir at room temperature for 2 hours to obtain a zinc-magnesium precursor; add 15mmol lithium hydroxide to 30ml ethanol and stir at room temperature for 2 hours to obtain an oxygen precursor; mix the zinc and magnesium precursors with the oxygen precursor at room temperature and stir for 10 hours, and repeatedly centrifuge and disperse with ethanol and heptane to obtain a magnesium-doped zinc oxide solution. The magnesium-doped zinc oxide solution is deposited on the first electron transport layer, and a second electron transport layer with a thickness of 15nm is formed after removing the solvent.

[0128] Step 3: Dispose green quantum dots (CdZnSe / ZnSe / CdZnS / ZnS) on the second electron transport layer to obtain a light-emitting layer with a thickness of 15 nm.

[0129] Step 4: In an inert atmosphere, spin-coat TFB (concentration of 8 mg / mL) on the light-emitting layer at a rotation speed of 3000 rpm for 30 s, and dry to remove the solvent to obtain a hole transport layer with a thickness of 80 nm.

[0130] Step 5: Spin-coat PEDOT:PSS on the hole transport layer at a rotation speed of 4000 rpm for 30 seconds, and dry to remove the solvent to obtain a hole injection layer with a thickness of 90 nm.

[0131] Step 6: By thermal evaporation, the vacuum degree is not higher than 3×10 -4 Pa, Ag is evaporated on the electron transport layer to obtain a first electrode with a thickness of 60 nm, and then encapsulated.

[0132] Device Example 2

[0133] This device embodiment is basically the same as device embodiment 1, with the only difference being that the thickness of the first electron transport layer is 20 nm, and the light-emitting layer is blue quantum dots instead of green quantum dots.

[0134] Device Example 3

[0135] This device embodiment is substantially the same as device embodiment 1, with the only difference being that in step 1, the device is refluxed at 80° C. for 4 hours in an inert gas atmosphere, and annealed after being heated at 500° C. for 10 mins in dry air.

[0136] Device Example 4

[0137] This device embodiment is substantially the same as device embodiment 1, with the only difference being that in step 1, magnesium acetate tetrahydrate is used instead of lithium acetate.

[0138] Device Example 5

[0139] This device embodiment is substantially the same as device embodiment 1, with the only difference being that in step 1, 3-aminopropanol is used instead of ethanolamine.

[0140] Device Example 6

[0141] This device embodiment is substantially the same as device embodiment 1, except that in step 1, 0.42 mmol of ethanolamine is added.

[0142] Device Example 7

[0143] This device example is substantially the same as device example 6, except that in step 1, 0.715 mmol of ethanolamine is added.

[0144] Device Comparison Example 1

[0145] The device comparison example is basically the same as device embodiment 1, with the only difference being that in step 1, the thickness of the first electron transport layer is 30 nm, the preparation of the second electron transport layer in step 2 is not performed, and the light-emitting device finally formed includes only the first electron transport layer, and does not include the second electron transport layer.

[0146] Device Comparison Example 2

[0147] This device embodiment is basically the same as device embodiment 1, with the only difference being that: step 1 is not performed, and the preparation of the second electron transport layer in step 2 is performed directly on the second electrode, and a second electron transport layer with a thickness of 30 nm is formed, and the light-emitting device finally formed only includes the second electron transport layer, and does not include the first electron transport layer.

[0148] Device Comparison Example 3

[0149] This device embodiment is basically the same as device embodiment 1, except that in step 1, a lithium-doped zinc oxide solution is prepared according to the method for preparing a magnesium-doped zinc oxide solution in step 2, wherein the molar ratio of lithium element to zinc element is 1: 10. The lithium-doped zinc oxide solution is then deposited on the bottom electrode, and a first electron transport layer with a thickness of 15 nm is formed after removing the solvent.

[0150] Device Comparison Example 4

[0151] This device embodiment is basically the same as device embodiment 2, with the only difference being that: step 1 is not performed, and the preparation of the second electron transport layer in step 2 is performed directly on the second electrode, and a second electron transport layer with a thickness of 35 nm is formed, and the light-emitting device finally formed only includes the second electron transport layer, and does not include the first electron transport layer.

[0152] test

[0153] The quantum dot light-emitting diodes of device embodiments 1-7 and device comparison examples 1-4 were tested, specifically including the turn-on voltage V@1nit, the maximum device efficiency CE@max at a current of 2mA, and the device life T95-1000 nit. The test data are shown in Tables 1 and 2, wherein Table 1 is the test data of the green quantum dot device, and Table 2 is the test data of the blue quantum dot device.

[0154] Among them, the external quantum dot efficiency EQE is the ratio of the number of electron-hole pairs injected into the quantum dot to the number of emitted photons, and the unit is %, which is an important parameter to measure the quality of electroluminescent devices and can be obtained by measuring with an EQE optical test instrument. The specific calculation formula is as follows:

[0155]

[0156] Where η eis the light output coupling efficiency, η r is the ratio of the number of recombined carriers to the number of injected carriers, χ is the ratio of the number of photon-generating excitons to the total number of excitons, K R is the radiation process rate, K NR is the rate of the non-radiative process.

[0157] Test conditions: carried out at room temperature, air humidity is 30-60%.

[0158] QLED device life: The time required for the device to reduce its brightness to a certain percentage of the maximum brightness when driven by a constant current or voltage. The time it takes for the brightness to drop to 95% of the maximum brightness is defined as T95, and this life is the measured life. In order to shorten the test cycle, the device life test is usually performed by accelerating device aging at high brightness with reference to the OLED device test, and the life under high brightness is obtained by fitting the extended exponential decay brightness attenuation fitting formula, for example: the life under 1000nit is calculated as T95-1000nit. The specific calculation formula is as follows:

[0159]

[0160] Where T95 L For lifespan at low brightness, T95 H is the measured lifetime under high brightness, L H To accelerate the device to the highest brightness, L L is 1000nit, A is the acceleration factor, for OLED, the value is usually 1.6~2. In this experiment, the lifespan of several groups of QLED devices at rated brightness was measured and the A value was 1.7.

[0161] The life test system is used to carry out life test on the corresponding devices. The test conditions are: at room temperature and the air humidity is 30-60%.

[0162] Table 1

[0163]

[0164] Table 2

[0165] CE@max(cd / A) V@1nit(V) T95-1000nit(h) Device Example 2 9 4.5 70 Device Comparison Example 4 12 4.8 45

[0166] Here, k represents thousand, for example, 4.5k=4500.

[0167] It can be seen from Table 1 and Table 2 that for green quantum dot devices, compared with device comparative examples 1-3, the arrangement of two electron transport layers in device embodiments 1-7, specifically including a first electron transport layer prepared by a sol-gel method and a second electron transport layer formed by a nano zinc oxide material prepared by a low-temperature alcohol phase method, can significantly reduce the turn-on voltage of the device, and has good current efficiency, and can improve the device efficiency without significantly increasing the device operating voltage. Specifically, it may be that the first electron transport layer can improve electron injection and transport, while the second electron transport layer close to the light-emitting layer reduces the dissociation of excitons at the interface between the two layers, thereby improving the device efficiency without significantly increasing the device operating voltage.

[0168] Similarly, for the blue quantum dot device, compared with the device comparison example 4, the device embodiment 2 can also significantly reduce the device's turn-on voltage, and has better current efficiency, and can improve the device efficiency without significantly increasing the device's operating voltage.

[0169] The light-emitting device and its preparation method, and the display device provided in the embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A method for preparing a light-emitting device, characterized in that: The preparation method comprises: Providing a preset device, the preset device comprising a second electrode; Providing an electronic functional layer on the preset device; A light-emitting layer and a first electrode are sequentially arranged on a side of the electronic functional layer away from the second electrode; or, The preparation method comprises: Providing a preset device, the preset device comprising a first electrode and a light-emitting layer; Providing an electronic functional layer on the preset device; Disposing a second electrode on the electronic functional layer at a side away from the light-emitting layer; Wherein, the electronic functional layer includes a first electron transport layer and a second electron transport layer; The step of providing an electronic functional layer on the preset device comprises: A first electron transport layer and a second electron transport layer are formed by a sol-gel method, wherein the second electron transport layer is arranged close to the light-emitting layer, and the first electron transport layer is arranged away from the light-emitting layer.

2. The preparation method according to claim 1, characterized in that The method of forming the first electron transport layer by a sol-gel method comprises: Providing a first solution, wherein the first solution includes a first metal source, an organic amine and a first solvent; subjecting the first solution to a reflux reaction to obtain a first sol; The first sol is disposed on the second electrode or the second electron transport layer to form a wet film, and annealing is performed to obtain the first electron transport layer.

3. The preparation method according to claim 2, characterized in that: The first metal source includes a first zinc source and a first doping metal source; further, the first zinc source includes one or more of diethyl zinc, zinc oleate, zinc stearate, zinc acetate, zinc laurate and zinc oxide; and / or, The first doping metal source includes one or more of a Li source, a Be source, a Mg source, an Al source, a K source, and a Ca source; and / or, The molar ratio of the zinc element in the first zinc source to the first doping metal element in the first doping metal source is (3-100):1; and / or, In the first solution, the total molar concentration of the zinc element in the first zinc source and the first doping metal element in the first doping metal source is 0.1 to 1 mmol / mL; and / or, The organic amine includes one or more of ethanolamine, diethanolamine, and 3-aminopropanol; and / or, The molar ratio of the organic amine to the first metal source is 1:1.3 to 1.3:1; and / or, The first solvent is selected from alcohol solvents.

4. The preparation method according to claim 2, characterized in that: The temperature of the reflux reaction is 50-80° C.; and / or, The reflux reaction time is 3 to 12 hours; and / or, The annealing temperature is 150-500° C.; and / or, The annealing treatment time is 5 to 120 minutes.

5. The preparation method according to claim 1, characterized in that: The forming of the second electron transport layer comprises: Providing a second solution, wherein the second solution includes a zinc oxide nanomaterial and a second solvent; The second solution is disposed on the light-emitting layer or the first electron transport layer to obtain the second electron transport layer.

6. The preparation method according to any one of claim 5, characterized in that: The zinc oxide nanomaterial is selected from zinc oxide or doped zinc oxide, wherein the doped zinc oxide includes zinc oxide and a second doping element, and the second doping element is selected from one or more of Mg, Ga, Al, Mn, and In; and / or, The second solvent is selected from alcohol solvents; and / or, In the second solution, the concentration of the zinc oxide nanomaterial is 10 to 50 mg / mL; and / or, The zinc oxide nano material is prepared by a low-temperature alcohol phase method.

7. A light emitting device, characterized in that: The light emitting device is prepared by the method for preparing the light emitting device according to any one of claims 1 to 6.

8. The light emitting device according to claim 7, characterized in that: The thickness of the first electron transport layer is 5 to 40 nm; and / or, The thickness of the second electron transport layer is 5-40 nm.

9. The light emitting device according to claim 7, characterized in that: The material of the light-emitting layer is selected from organic light-emitting materials or quantum dot light-emitting materials; the organic light-emitting material is selected from at least one of diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives or fluorene derivatives, TBPe fluorescent materials emitting blue light, TTPA fluorescent materials emitting green light, TBRb fluorescent materials emitting orange light and DBP fluorescent materials emitting red light; the quantum dot light-emitting material is selected from at least one of single-structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials, the single-structure quantum dots are selected from at least one of II-VI compounds, IV-VI compounds, III-V compounds and I-III-VI compounds, the II - Group VI compounds are selected from CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS , CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZn The IV-VI group compound is selected from at least one of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, and the III-V group compound is selected from at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, at least one of GaPAs, GaPSb, AlNPs, AlNAs, AlNSb, AlPAs, AlPSb, InNPs, InNAs, InNSb, InPAs, InPSb, GaAlNPs, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNPs, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNPs, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the Group I-III-VI compound is at least one of CuInS, CuInSe and AgInS;The core of the quantum dots of the core-shell structure is selected from any one of the above-mentioned single-structure quantum dots, and the shell material of the quantum dots of the core-shell structure is selected from at least one of CdS, CdTe, CdSeTe, CdZnSe, CdZnS, CdSeS, ZnSe, ZnSeS and ZnS; the perovskite semiconductor material is selected from doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors; the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2 + Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of the following; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ At least one of, X is a halogen anion selected from Cl - Br - ,I - At least one of; and / or, The first electrode and the second electrode are independently selected from metal electrodes, carbon electrodes, doped or undoped metal oxide electrodes and composite electrodes; wherein the material of the metal electrode is selected from at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Ni, Ir and Mg; the material of the carbon electrode is selected from at least one of graphite, carbon nanotubes, graphene and carbon fiber; the material of the doped or undoped metal oxide electrode is selected from ITO, FTO, ATO, AZO, GZO, IZO, MZO, ITZO, ICO, At least one of AMO, SnO2, In2O3, Cd:ZnO, F:SnO2, In:SnO2, and Ga:SnO2; the material of the composite electrode is selected from at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, and ZnS / Al / ZnS; and / or, The light-emitting device further comprises a hole functional layer, which is arranged between the first electrode and the light-emitting layer. The hole functional layer comprises at least one layer of a hole injection layer and a hole transport layer. The material of the hole transport layer is selected from arylamine, polyaniline, polypyrrole, poly(p-phenylene vinylene) and its derivatives, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, poly(N-vinyl carbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octyl)-1,1'-biphenyl compound, poly(p-carbazolyl ... Fluorene) and its derivatives, poly (spirofluorene) and its derivatives, doped or undoped NiO, MoO3, WO3, V2O5, CrO3, CuO, MoS2, MoSe2, WS3, WSe3, CuS, CuSCN one or more; wherein the aromatic amine is selected from 4,4'-bis (9-carbazole) biphenyl, poly (9,9-dioctylfluorene-CO-N- (4-butylphenyl) diphenylamine), poly (N,N'-bis (4-butylphenyl) -N,N'-bis (phenyl) benzidine), N,N'-bis (4- (N,N'-diphenyl-amino) phenyl )-N,N'-diphenylbenzidine, poly(9,9-dioctylfluorene-co-bis-N,N-phenyl-1,4-phenylenediamine), 4,4',4"-tri(carbazol-9-yl)triphenylamine, 4,4',4"-tri(N-carbazolyl)-triphenylamine, 4,4',4"-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-1,1'-biphenyl-4,4'-diamine, N,N'- One or more of diphenyl-N,N'-(1-naphthyl)-1,1'-biphenyl-4,4'-diamine, Spiro-NPB, Spiro-TPD, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, Spiro-NPB; the poly(p-)phenylene vinylene and its derivatives are selected from one or more of poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] and poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene];The material of the hole injection layer is selected from poly(ethylenedioxythiophene): polystyrene sulfonate, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanoquinone-dimethane, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, copper phthalocyanine, poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine, 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl, 4,4',4"-tris[phenyl(m-tolyl)amino]triphenylamine, 4,4' ,4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenylcyclohexane, 4,4',4"-tri(diphenylamino)triphenylamine doped with F4-TCNQ, p-doped phthalocyanine, F4-TCNQ doped N,N'-diphenyl-N,N'-di(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, transition metal oxides, transition metal sulfur compounds; wherein the transition metal oxides include one or more of NiO, MoO2, WO3, and CuO; the metal sulfur compounds include one or more of MoS2, MoSe2, WS3, WSe3, and CuS.; 10. A display device, characterized in that: Comprising a light emitting device as described in any one of claims 7 to 9.